Planeamiento de Sistemas de Distribución de Energía Eléctrica Usando Branch and Bound - Granada Echeverri, Mauricio; Gallego Rendón, Ramón Alfonso; Hincapié Isaza, Ricardo Alberto (Ingeniería, 2004)
This paper presents a Branch and Bound algorithm to solve the planning problem of the electrical energy Distribution Systems considering the dimension and location of new substations, as the way of new primary feeders too. The mathematical model employed is clasified as Mixed Integer Linear (PLEM), the model presents combinatorial explosion.